Digital Educational Technologies and New Sociabilities in an African University Context - (:unkn) unknown (My University, 2024)
In Europe, America and Asia, research into the uses of digital educational technologies and their contributions to teaching and learning has flourished, while in Sub-Saharan Africa, with the exception of a few rare studies in educational science, research has long neglected these uses. The literature highlights shortcomings in terms of access to equipment and interest in certain technical devices. The most widely adopted technology is the cell phone, which is used for both personal and school purposes (Maïdakouale and Fagadé, 2022). This study aims to support the integration of educational digital technologies among a young population already possessing non-formal digital skills. We study the social logics structuring the uses that, themselves, feed them (Paquienséguy, 2012). We also highlight the "new" school sociabilities that these uses bring. As Leveratto and Leontsini (2008) point out, interest in the educational uses of the Internet also requires us to explore its playful and social dimensions, since social availability determines personal commitment to intensive use. We used qualitative and quantitative methods to survey 292 students in Burkina Faso, Gabon and Niger. We show that socio-technical and economic factors are involved in accompanying the digital revolution in these universities from behind the scenes.
Keywords: African Research